(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
The background of this research is based on the legal complexity and social implications that arise in the annulment of birth certificates of adopted children, especially related to the protection and rights of children and legal certainty in population administration. The formulation of the problem in this research includes how the legal considerations of the Supreme Court in canceling the birth certificate of adopted children, the application of the principles of legal certainty and protection of children’s rights, and the relevance of Islamic law principles in this context. The research objectives are to understand the legal process of cancelling an adopted child’s birth certificate, analyze its impact on children’s rights, and examine the suitability of the Supreme Court’s decision with national and Islamic legal principles. The research method used is qualitative with a descriptive-analytic approach, which involves document study, interviews, and field observations to obtain in-depth and contextual data. The results show that the Supreme Court emphasized the importance of a strong legal basis and proper procedures in cancelling the certificate. The decision rejected the cassation because there was no valid legal reason to cancel the deed, and emphasized the importance of maintaining the psychological stability and legal identity of the child. The principles of legal certainty and child protection are the main basis for the decision. In Islamic law, annulment is possible if there is a violation of the principle of nasab, which requires clarity of lineage. Conclusion: This research is expected to contribute to the development of a fairer and more comprehensive legal policy.